Pengaruh Leadership Terhadap Motivasi Kerja Karyawan - Ananda, M. Risqi; Rahmah, Alvia; Rifani, Devi; Maylani, Nirma (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Leadership is one of the main factors that influence employee motivation in an organization. This article aims to analyze the effect of leadership style on employee work motivation. This research uses the literature study method by reviewing various theories and previous research related to the relationship between leadership and motivation. The results of the study show that leadership has a significant positive impact on employee work motivation. Leadership style is able to inspire employees, encourage creativity, and increase the sense of individual responsibility for organizational goals. Therefore, leaders who are able to implement leadership styles tend to create a more productive and harmonious work environment.